Causal Relationship Between Parathyroid Hormone and the Risk of Osteoarthritis: A Mendelian Randomization Study - Huang, Guiwu; Zhong, Yanlin; Li, Wenchang; Liao, Weiming; Wu, Peihui (Frontiers in Genetics, 2021)
Abstract: Background: Previous studies have demonstrated an inverse association between parathyroid hormone (PTH) and the risk of osteoarthritis (OA). However, it remains unknown whether such association reflect causality. We aimed to apply a Mendelian randomization (MR) approach to investigate the causal association between PTH and OA. Methods: We performed a two-sample MR analysis using summary statistics from 13 cohorts (PTH, N = 29,155) and a recent genome-wide association study meta-analysis (OA, N = 455,221) by the UK Biobank and Arthritis Research UK OA Genetics (arcOGEN). MR analyses were carried out mainly using the inverse-variance weighted method. Sensitivity analyses were performed to test the robustness of the associations using the weighted median method, the MR-Egger method, and “leave-one-out” analysis. Analyses were performed again to test whether the associations remained statistically significant after excluding any outlier variants that were detected using the MR-PRESSO (Mendelian Randomization Pleiotropy RESidual Sum and Outlier) test. Results: Five single nucleotide polymorphisms (SNPs) selected as instrumental variables at the genome-wide significance threshold (p < 5×10−8). The causal effect between PTH and OA was genetically predicted using the inverse-variance weighted method (odds ratio = 0.67, 95% confidence interval: 0.50–0.90; p = 0.008). This result was borne out using the weighted median method (odds ratio = 0.73, 95% confidence interval: 0.60–0.90; p = 0.004). The causality remained robust after discarding the outlier variants as well as SNPs associated with confounding factors. Conclusions: MR analysis supported a potential causative relationship between decreased serum circulating PTH and a higher risk of hip and knee OA. Keywords: Parathyroid hormone, Osteoarthritis, Mendelian randomization analysis, Genome-wide association studies (GWAS), Single nucleotide polymorphisms (SNPs)